Transverse momentum spectra of charged particles in proton-proton collisions at √s=900 GeV with ALICE at the LHC - Aamodt, Kenneth; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; Schicker, Rainer; Schweda, Kai; et al. (Physics letters, 2010)
The inclusive charged particle transverse momentum distribution is measured in proton-proton collisions at s=900 GeV at the LHC using the ALICE detector. The measurement is performed in the central pseudorapidity region (|η|<0.8) over the transverse momentum range 0.15<pT<10 GeV/c. The correlation between transverse momentum and particle multiplicity is also studied. Results are presented for inelastic (INEL) and non-single-diffractive (NSD) events. The average transverse momentum for |η|<0.8 is 〈pT〉INEL=0.483±0.001 (stat.)±0.007 (syst.) GeV/c and 〈pT〉NSD=0.489±0.001 (stat.)±0.007 (syst.) GeV/c, respectively. The data exhibit a slightly larger 〈pT〉 than measurements in wider pseudorapidity intervals. The results are compared to simulations with the Monte Carlo event generators PYTHIA and PHOJET.
*ALICE Collaboration: K. Aamodt, V. Angelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, J. Mercado Pérez, K. Oyama, Y. Pachmayer, R. Schicker, K. Schweda, H.K. Soltveit, J. Stachel, S. Vallero, B. Windelband (und 1046 weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 14.11.2022